Purwarupa Arsitektur E-government Berbasis Service Oriented Architecture - Pantjawati Sudarmaningtyas; Lukito Edi Nugroho; Eko Nugroho (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2012)
E-government (e-gov) classified into four levels, the first is information publication through the website, second is interaction between society and government. The third is transactions between the community and government and the fourth is integration of all government offices. Service Oriented Architecture (SOA) is framework that has properties of loosely coupled, highly interoperable, reusable, and interoperability. It has potential connecting diversity of platforms without make changes to the application and the database that already exists. Currently Sidoarjo has e-gov first level and most depart-ment/agency already has applications and databases, but it can’t communicate with each other because of diversity of appli-cations/platforms. The study aims build prototype of e-gov third level by increasing cohesion between services and the interope-rability of data/applications. The research used Shared Service Life Cycle (SSLC) method, consists of business process identi-fication, analysis, design and development, and evaluation. The study produced a prototype e-gov third level SOA-based that has cohesion between services and the interoperability of data/appli-cations.